Agrio et Emulsio – development of fruity mustard creams - Basto De Lima, Maria Gabriela (2018)
Agrio et Emulsio project (POCI-01-0145-FEDER-023583) presents an proposal in the areas of vinegar products and food emulsions. Combining technical features with mediterranean traditions and Nouvelle Cuisine, two prototypes of fruity mustards are undergoing final development, valuing regional raw materials and profiling into the gourmet/vegan/veggie markets. Mustard creams are oil-in-water emulsions but its practice is linked to vinegar traditions since the thirteenth century, in France, with the foundation of the first confraternity of Maîtres Vinaigrier-Moutardier. Thus, by applying the ancestral practice, mustard (seeds, fragments, powder) was first submitted to maturation studies, varying the type of vinegar and the time of immersion/contact. Maturation reached equilibrium on the 16th day, but pH evolution shows a practically stationary state from the 7th. Best results were obtained with seeds and powdered mustards in red wine vinegar, 4 %(m/v) acidity. The assays were carried out at room temperature using Sinapis Alba (Linnaeus) mustard species. Prototyping articulated technical, analytical (physicochemical, rheological, microbiological) and sensory tests. Each final prototype has a distinct profile of ingredients, mustard, fruits (raspberry and beet or blueberry), olive oil, water, salt, sugar, honey and spices. Both creams retain the sui generis taste of mustard tinted with the fruit flavour plus an innovative pink colour.